INTERNALIZING THE VALUES OF RELIGIOUS MODERATION IN “JEDA NULIS” CHANNEL FOR MILLENIALS - M. Riyan Hidayat (Balai Diklat Keagamaan Bandung, 2022)
The bombing of the Makassar Cathedral Church and the shooting at the National Police Headquarters reflects radicalism among the youth. The two perpetrators before carrying out their actions both wrote messages to their families that they were ready to be martyred to carry out jihad as the highest practice in Islam. The internalization of radicalism among millennials through religious propaganda on social media shows the importance of platforms to counter these issues. Therefore, the author makes phenomenological research using the concept of internalization as the formal and material object in form of videos on the